KAPASITAS FISKAL DAN PDRB DENGAN TINGKAT KEMISKINAN: STUDI PADA KABUPATEN/KOTA DI SULAWESI TENGAH (2009-2013) - Rauf, A. Alimuddin (Katalogis, 2016)
This study aims to measure and identify local fiscal capacity in the implementation of fiscal decentralization, and simultaneously measuring the relationship between the fiscal capacity of the area and the GDRP against poverty. Variables used in this research are the fiscal capacity, Gross Domestic Regional Product (GDRP), and a variable poverty. The data used in this research is secondary data from 10 district and one city in the province of Central Sulawesi with a period of 2009 - 2013. In general, the study concluded that the Gross Domestic Regional Product (GDRP) and the fiscal capacity of a statistically significant effect on poverty, which means that the fiscal capacity in 10 district and one city in the Province of Central Sulawesi could be improved to encourage economic growth. Government policies in the budget affect the capacity of the fiscal, economic growth, and poverty in the Province of Central Sulawesi. Recommendations from this study is that the local government should be concerned about the increase in fiscal capacity and Gross Domestic Regional Product (GRDP) and local governments are required to increase their responsibilities so that all areas can improve their welfare.